Groundwater damages on the historic buildings of Cairo: the case of the medieval walls of Mokattam limestone. Issue 1 (November 2020) - Coppola, M; Di Benedetto, F; Garzonio, CA; Pecchioni, E; Santo, AP
Abstract: The conservation of historical buildings in Cairo represents a complex matter, influenced by several key factors such as the cultural context, the intrinsic features of a vast and heterogeneous architectural heritage and the environmental conditions. An Italian-Egyptian research group is working on the peculiarities of the monument conservation in old Cairo, concerning the material decay in relation to the anthropic and climatic factors and the pollution levels. Monument vulnerability levels strongly need to be identified and systematized to delineate adequate programs of control, management and intervention. One of the main topics developed is the study of the deterioration mechanisms of stone materials in medieval walls, connected to the capillary damp rising from the ground, common in Egypt, always accentuated by the combination with other factors. The research examines some historic buildings in different areas (El-Gamaleya, El Darb El Ahmar, Al Qarafah). The variety of materials has led to limiting the first phases of the study to the masonry materials, with special attention to the limestone blocks. The intersection of data collected on the field with those relating to underground water and environmental factors has allowed us to focus on some aspects of the problem. Some syntheses have been proposed on the main mechanisms affecting the studied material in situ and the necessary directions for further investigation have been identified. Our first results highlight the relationship existing between the environmental thermo-hygrometric excursions and the capillary water rising from the ground, which affect the evaporation speed, the imbibition levels and the crystallization of salts inside and on the rock surface. The studied rocks display intense weathering (decohesion, dissolution) due to a number of chemical and physical phenomena, responsible for a generalized decay of the mechanical properties of the original material. The observed widespread phenomena of carbonate sulphation also suggest the atmospheric contribution of particulate matter and polluting compounds. The mineralogical and physical characterization of the limestone allowed us to estimate its resistance to the decay processes.